Therapeutic Management of Congestive Heart FailureSecondary to Dilated Cardiomyopathy in a Male LabradorDog: A Case Report - Bhuyan, Udipta; Sandilya, Anindita (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Dilated cardiomyopathy (DCM) is characterized by significant systolic dysfunction and expansion of the heart chambers (Oyama, 2015). In dogs, DCM is one of the most prevalent acquired cardiovascular conditions. Since idiopathic DCM accounts for the majority of cases in dogs, most treatments are categorized as ‘‘Band-Aid therapies,’’ which temporarily relieve symptoms but don’t address the underlying source of the illness (Sanderson, 2006). Without any indication of heart symptoms, the concealed stage of this illness is typified by structural or electrical alterations. The main morphologic signs of systolic dysfunction are left and rarely right ventricular dilatation in systole and later diastole. Ventricular premature complexes are the most common type of electrical abnormalities (Wess et al., 2017). Clinical indicators of congestive heart failure (CHF), such as elevated respiratory rate, dyspnoea, coughing, or exercise intolerance, are what define the overt stage of the condition (Friederich et al., 2020). The present report describes a case of congestive heart failure secondary to dilated cardiomyopathy in a Labrador dog and its successful therapeutic management.